Jejak karbon pada tahap operasional agro-eduwisata kota mataram menggunakan pendekatan penilaian daur hidup - Joni Safaat Adiansyah (Universitas Gadjah Mada, 2022)
Climate change is one of the global issues that require the participation of all stakeholders for handling. In addition, the climate change issue is listed as one of the sustainable development goals (SDGs). The Government of Mataram city, as one of the stakeholders, has committed to involve the climate change consideration into its planned program, including the development of agro-edutourism facility. This study aims to calculate a carbon footprint of agroedutourism facility during the operational stage in order to implement the Greenhouse Gas (GHG) emission reduction strategy. The method used is a life cycle assessment approach with ReCiPe analysis, and the functional unit is an annual carbon footprint per m2 area of agro-edutourism. The study showed that the total carbon footprint per m2 was 2.88 KgCO2-e per annum with the primary environmental hotspot was fossil fuel utilization in energy source of agro-edutourism facility (Electricity State-own Company) and visitor vehicles. Therefore, some strategies could be applied for reducing the carbon footprint, such as increasing the utilization percentage of renewable energy (solar panel), using energy-saving bulbs, preparing the facilities for zero-emission vehicles, and applying the green building concept or design. Further research is required to assess the energy management concept from the technical feasibility aspect and economic aspect for complimenting this study.